2016
DOI: 10.1038/srep22071
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Temperature Difference in Neuronal Cells

Abstract: For a better understanding of the mechanisms behind cellular functions, quantification of the heterogeneity in an organism or cells is essential. Recently, the importance of quantifying temperature has been highlighted, as it correlates with biochemical reaction rates. Several methods for detecting intracellular temperature have recently been established. Here we develop a novel method for sensing temperature in living cells based on the imaging technique of fluorescence of quantum dots. We apply the method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 46 publications
(70 reference statements)
3
91
0
1
Order By: Relevance
“…Recent studies have identified temperature heterogeneity in neuronal cells, 24 however debate remains about whether biochemical reactions at the single cell level are sufficient to generate such heterogeneity. 35,36 Other forms of temperature variations have been proposed which may accompany current flow in open ionic channels 37 .…”
Section: Wide-field Imaging and Odmr Spectroscopy Of Ndsmentioning
confidence: 99%
“…Recent studies have identified temperature heterogeneity in neuronal cells, 24 however debate remains about whether biochemical reactions at the single cell level are sufficient to generate such heterogeneity. 35,36 Other forms of temperature variations have been proposed which may accompany current flow in open ionic channels 37 .…”
Section: Wide-field Imaging and Odmr Spectroscopy Of Ndsmentioning
confidence: 99%
“…An alternative method makes use of spectroscopic techniques, including optical interferometry [359,360], Raman spectroscopy [361] and luminescence [362][363][364][365][366]. The technical details of the above spectroscopic techniques can be found in relevant reviews [367][368][369][370].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…Therefore, QDs or NRs with sizable QCSE (at room temperature) that are properly inserted into the cell membrane could report on changes in membrane potential via a spectral shift, a change in the emission intensity, and/or a change in the excited state lifetime. QCSE-based QDs /NRs voltage sensors could also offer several advantages over existing voltage sensors based on organic dyes, fluorescent proteins, or their hybrid: they (1) have high voltage sensitivity (quantified as percent change in fluorescence intensity, ΔF/F), (2) exhibit large spectral shifts (Δλ) enabling ratiometric detection, (3) exhibit changes in excited state lifetime (providing alternative detection scheme), (4) have high brightness affording single-particle detection and superresolution recording, (5) have a fast response time (~ns) based on QCSE, (6) have highly functionalizable surface, (7) have emission wavelength and quantum yield (QY) that can be engineered, (8) have negligible photobleaching, and (9) have low cytotoxicity (after surface modification). With the extremely fast response time, QDs /NRs will be capable of reporting and resolving the APs, which not only have fast dynamics (sub-ms) but also present in a wide range of frequencies and waveforms, especially in mammalian brains [38][39][40][41][42][43] .…”
mentioning
confidence: 99%